FROM EFFECTIVENESS TO EMPOWERMENT: REVEALING THE IMPACT OF WOMEN ENTREPRENEURS ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN JABODETABEK - Oscar Jayanagara; Cindy Claudia (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This study aims to analyze the influence of Women's Entrepreneurial Effectuation (WEE) on Structural Empowerment (SE), Psychological Empowerment (PE), and SME Employee Performance (EP), as well as the moderating role of Gender Equality (GE) and Market Orientation (MO) on female employees working in MSMEs in the Greater Jakarta area. This study uses a quantitative method with a descriptive approach and judgment sampling technique on 330 respondents. Primary data were collected through questionnaires and analyzed using Partial Least Square (PLS). The results of the study show that Women's entrepreneurial effectuation does not have a positive influence on structural empowerment, Women's entrepreneurial effectuation has a positive influence on psychological empowerment, Women's entrepreneurial effectuation does not have a positive influence on SME employee performance, Gender equality as a moderating variable cannot strengthen the relationship between women's entrepreneurial effectuation on structural empowerment and SME employee performance, Gender equality as a moderating variable can strengthen the relationship between women's entrepreneurial effectuation on psychological empowerment, Structural empowerment does not have a positive influence on SME employee performance, Structural empowerment as a mediating variable cannot strengthen the relationship between women's entrepreneurial effectuation on SME employee performance, Psychological empowerment has a positive influence on SME employee performance, Psychological empowerment as a mediating variable can strengthen the relationship between women's entrepreneurial effectuation on SME employee performance, Market orientation as a moderating variable can strengthen the relationship between structural empowerment on SME employee performance, Market orientation as a moderating variable cannot strengthen the relationship between women's entrepreneurial effectuation and psychological empowerment on SME employee performance. These findings emphasize the importance of women's entrepreneurial effectuation in improving performance through structural empowerment. and market orientation support. Practically, this research provides recommendations for female MSMEs to integrate an effectuation approach with empowerment and market orientation strategies to improve business competitiveness and performance.